2023
DOI: 10.15244/pjoes/163568
|View full text |Cite
|
Sign up to set email alerts
|

How Does Export Behavior Affect Carbon Emissions? Multivariate Heterogeneous Data Based on Chinese Enterprises

Abstract: Since the beginning of its reform and opening up period, China's economy has been growing rapidly, and thus, environmental problems have become increasingly prominent [1,2]. The demand for fossil energy for human activities has generated a large amount of carbon emissions, which have led to global warming with the threat of irreversible disasters occurring on the planet [3]. The sixth Intergovernmental Panel on Climate Change (IPCC) assessment report (2022) pointed out that the average annual global greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Therefore, it is preliminarily concluded that the four technological progress paths promote improvements in export product quality. Our preliminary conclusion is also reinforced by the findings of these studies (X. Li & Xiao, 2020; H.…”
Section: Empirical Results and Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, it is preliminarily concluded that the four technological progress paths promote improvements in export product quality. Our preliminary conclusion is also reinforced by the findings of these studies (X. Li & Xiao, 2020; H.…”
Section: Empirical Results and Analysissupporting
confidence: 82%
“…Some scholars have also studied the direct relationship between the two, but the findings are not uniform. X. Li and Xiao (2020) argue that firm R&D improves export product quality in two ways: first, by generating new technologies that increase the exports of technology-intensive products, and second, by increasing firm productivity, reducing production costs, and expanding exports of capital-intensive products.…”
Section: Literature Review and Summarymentioning
confidence: 99%